IMPROVING LEARNING CONCENTRATION THROUGH DIFFERENTIATED LEARNING IN CONTENT ASPECTS OF 4TH GRADE SD NEGERI 94 PALEMBANG - Dewi, Lutvi Arsita; Indaryanti, Indaryanti (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2023)
This research was motivated by the low level of student learning concentration. The purpose of this research was to make efforts to improve learning concentration through differentiated instruction in content aspects. This class action research was conducted in two cycles using the Kemmis & Taggart model. The subjects of this study were 23 students in 4th grade (A class) at State Elementary School 94 Palembang. This research aimed to enhance the learning concentration among 4th grade students at SD Negeri 94 Palembang through differentiated instruction in aspect content. The data collection technique used Likert scale questionnaires. The data analysis techniques used are both quantitative and qualitative analysis. The results of the pre-cycle research revealed that the learning concentration was 43.47% (low). In the cycle I, the learning concentration increased to 69.56% (moderate), and it further increased to 86.95% (high) in the cycle II. These results indicate that differentiated instruction successfully improved the learning concentration of 4th grade students at SD Negeri 94 Palembang.